Maori Self-Determination: Towards Differentiated Liberal Citizenship - O'Sullivan, Dominic (Australian Journal of Politics & History, 2019)
During the 1980s and 1990s biculturalism was the ascendant political philosophy for managing the relationship between the New Zealand Crown and the indigenous Maori population. Biculturalism understood Maori politics as a partnership between Maori and the state, grounded in the Treaty of Waitangi, the agreement signed in 1840 from which British government was established. Biculturalism was presented as morally superior to multiculturalism which was understood as setting aside Maori Treaty rights and rights of prior occupancy in favour of less substantive rights available to Maori as one of many ethnic minorities. However, a deeper reading of multicultural political theory provides an instructive critique of biculturalism's inherent limits from the perspective of the Maori right to self-determination. It shows why biculturalism's influence waned. It also shows why Matike Mai o Aotearoa, a blueprint for constitutional transformation commissioned by tribal leaders is unlikely to succeed as a contemporary attempt to reassert biculturalism's influence. Multicultural theory is not a panacea for the right to self-determination, but it does not restrict the development of a broader Maori-centred differentiated liberal citizenship in the ways that biculturalism precludes.
Keywords: Biculturalism; Multicultural; Politics; Self-Determination